Alternagin-C, a disintegrin-like protein from the venom of Bothrops alternatus, modulates alpha2ß1 integrin-mediated cell adhesion, migration and proliferation - Selistre-de-Araujo,H.S. (2005)
The alpha2ß1 integrin is a major collagen receptor that plays an essential role in the adhesion of normal and tumor cells to the extracellular matrix. Alternagin-C (ALT-C), a disintegrin-like protein purified from the venom of the Brazilian snake Bothrops alternatus, competitively interacts with the alpha2ß1 integrin, thereby inhibiting collagen binding. When immobilized in plate wells, ALT-C supports the adhesion of fibroblasts as well as of human vein endothelial cells (HUVEC) and does not detach cells previously bound to collagen I. ALT-C is a strong inducer of HUVEC proliferation in vitro. Gene expression analysis was done using an Affimetrix HU-95A probe array with probe sets of ~10,000 human genes. In human fibroblasts growing on collagen-coated plates, ALT-C up-regulates the expression of several growth factors including vascular endothelial growth factor, as well as some cell cycle control genes. Up-regulation of the vascular endothelial growth factor gene and other growth factors could explain the positive effect on HUVEC proliferation. ALT-C also strongly activates protein kinase B phosphorylation, a signaling event involved in endothelial cell survival and angiogenesis. In human neutrophils, ALT-C has a potent chemotactic effect modulated by the intracellular signaling cascade characteristic of integrin-activated pathways. Thus, ALT-C acts as a survival factor, promoting adhesion, migration and endothelial cell proliferation after binding to alpha2ß1 integrin on the cell surface. The biological activities of ALT-C may be helpful as a therapeutic strategy in tissue regeneration as well as in the design of new therapeutic agents targeting alpha2ß1 integrin.